Repositori Berbasis Web Fakultas Sains Dan Ilmu Komputer Universitas Muhammadiyah Gorontalo - Lamusu, Rizal; Maku, Rubiyanto; Ibrahim, Irawan; Gobel, Alvian Van (Jurnal Ilmu Komputer (JUIK), 2024)
The Faculty of Science and Computer Science, Muhammadiyah University of Gorontalo is a higher education entity that has various needs in managing and utilizing data, information and important documents. This research aims to design a web-based repository for the Faculty of Science and Computer Science, Muhammadiyah University of Gorontalo and implement a web-based repository at the Faculty of Science and Computer Science, Muhammadoyah University of Gorontalo. This research was developed using a prototype model, PHP programming language, Laravel framework, MySQL and system design tools using Unified Modeling Language. The results of research using a prototype system development model show that the Web-Based Repository System, Faculty of Science and Computer Science, Muhammadiyah University, Gorontalo has reached the maturity level. which allows its effective use. With this system, it is hoped that employees of the Head of Administration and his staff at the Faculty of Science and Computer Science, Muhammadiyah University of Gorontalo can implement a web-based repository that is effective, efficient, and in accordance with academic and administrative